2022
DOI: 10.1097/cce.0000000000000638
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Variation in Management and Outcomes of Acute Respiratory Distress Syndrome Due to COVID-19

Abstract: OBJECTIVES: To describe hospital variation in use of “guideline-based care” for acute respiratory distress syndrome (ARDS) due to COVID-19. DESIGN: Retrospective, observational study. SETTING: The Society of Critical Care Medicine’s Discovery Viral Infection and RESPIRATORY ILLNESS UNIVERSAL STUDY COVID-19 REGISTRY. PATIENTS: Adult patients with ARDS due to COVID-19 between February 15, 2020, and April 12, 2021. INTERVENTIONS: Hospital-level use of “guideline-based care” for ARDS including low-tidal-vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…Despite well established, evidence-based principles for lung protective ventilation, 4 , 5 wide variation in the management of ARDS across hospitals continues in practice, with up to half of patients not receiving care consistent with guideline recommendations during the first year of the COVID-19 pandemic. 80 The identification of driving pressure as an important prognostic factor, based on high-certainty evidence, is consistent with existing evidence showing that this ventilation variable is strongly associated with mortality in patients with ARDS. 81 , 82 Additionally, we found that a longer duration of invasive mechanical ventilation (most commonly defined by a 7-day threshold) and a higher PaCO 2 are poor prognostic signs.…”
Section: Discussionsupporting
confidence: 83%
“…Despite well established, evidence-based principles for lung protective ventilation, 4 , 5 wide variation in the management of ARDS across hospitals continues in practice, with up to half of patients not receiving care consistent with guideline recommendations during the first year of the COVID-19 pandemic. 80 The identification of driving pressure as an important prognostic factor, based on high-certainty evidence, is consistent with existing evidence showing that this ventilation variable is strongly associated with mortality in patients with ARDS. 81 , 82 Additionally, we found that a longer duration of invasive mechanical ventilation (most commonly defined by a 7-day threshold) and a higher PaCO 2 are poor prognostic signs.…”
Section: Discussionsupporting
confidence: 83%
“…Our study captured intensivist workload, measured as the number of patients cared for. Study ICUs were primarily recruited through SCCM’s Discovery Network and were similar to ICUs and patients represented in other Discovery network studies ( 32 , 33 ). The overall prevalence of burnout in our cohort of ICU physicians was 26.4%, and there was no difference in the prevalence of burnout between physicians with high workload (>14 patients per physician) versus low workload (≤14 patients per physician).…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, some studies suggested that 25-62% of patients with COVID-19associated ARDS were managed with prone positioning (14)(15)(16)(17)(18)(19). However, whether this greater use of proning was concordant with evidence-based recommendations (i.e., proning sessions of at least 12-16 consecutive hours (hr) in early moderate-to-severe ARDS) (1,4) is unknown.…”
mentioning
confidence: 99%